Decision Model for Assessing Healthcare Ict Support Implications: User Perception - Watkins-Orellana, F; Oddershede-Herrera, A; Cordova-Gonzalez, F (Agora University, 2014)
This paper presents a multi-criteria decision model based upon user judgments to assist the evaluation process of an Information and Communication Technology (ICT) network system in health care to improve the quality of service (QoS). Measuring quality in health care services is not an easy task, as there are many competing goals involved, human, economic, communications technology, governmental and others. Integrating multiple criteria decision analysis (MCDA) methodology with modeling and simulation through Optimization Network Engineering Tool (OPNET) platform permit to characterize main ICT user and identify priority applications to examine network QoS requirements and implications. The proposed approach permitted to identify the main users, to elaborate a profile and characterization of the ICT support requirements according to their main daily task in answer to a service requirement. The results generate evidence related to the important factors effecting quality in hospital requirement as availability of services and the need for ubiquitous access to integrated information. The stakeholder interface perception and resources for ICT network support are investigated through a case study for Chilean hospitals. © 2006-2014 by CCC Publications.